El doctoral ovetense Pedro Cienfuegos, Grado (Asturias), 1642- + Oviedo, 1684 - García Sánchez, Justo (Revista española de derecho canónico, 2014)
Pedro Díaz de Cienfuegos or Pedro Cienfuegos Agüelles is born in Grado (Asturias), in October, 1642. He studies Law in Oviedo and Salamanca, where he was a scholar in San Pelayo of Green and Santiago of the Zebedeo of Cuenca, graduating in utroque Iure. Penitentiary canon in Coriás cathedral (Caceres), in 1673 and governor of the bishopric, obtained in July, 1680 the doctoral canonry of the cathedral of Oviedo, up to his death on December 1 of 1684. It intervened actively as legal adviser of you them will come to terms, whose principal business are described, with the opinion issued by the Asturian canonista, it brings over of the collation of the canonry of the penitientary one in the cathedral corporation